The body farm - Cornwell, Patricia Daniels, 1953- (Warner Books, 1995)
Black Mountain, North Carolina: a sleepy little town where the local police deal with one homicide a year, if they're unlucky, and where people are still getting used to the idea of locking their doors at night. But violent death is no respecter of venue, and the discovery of the corpse of the corpse of an 11-year-old girl sends shock waves through the community. Dr Kay Scarpetta, Chief medical Examiner on a similar case in Virginia, is called in to apply her forensic skills to this latest atrocity, but the apparent simplicity of the case proves something of a poisoned chalice - until Scarpetta finds enlightenment through the curious pathologists' playground known as the Body Farm ...